2021
DOI: 10.3390/healthcare9091173
|View full text |Cite
|
Sign up to set email alerts
|

Effective Preventive Strategies to Prevent Secondary Transmission of COVID-19 in Hemodialysis Unit: The First Month of Community Outbreak in Taiwan

Abstract: Background: Dialyzed patients are vulnerable to coronavirus infection disease 2019 (COVID-19). The incidence and outcome of COVID-19 in hemodialysis (HD) patients in Taiwan remain unclear. A series of preventive measures were executed to combat COVID-19 transmission among HD patients. Methods: We carried out a series of forward-looking and practical preventive strategies of COVID-19 control in our HD center. Incidences of COVID-19 of our HD unit were compared with those of national and local estimates from a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…The differential impact of fear between Hong Kong and Taiwan suggests that the association between fear of COVID-19 and personal hygiene practices may need to be induced when the pandemic severity achieves a certain level. Such an observation echoes with a recent study capturing the temporal change in COVID-19 severity in Taiwan that the association between fear and protective behaviors was not significant during March and May 2020 but became significant during May and July 2021 when the largest COVID-19 outbreak in Taiwan was emerging ( 64 ).…”
Section: Discussionsupporting
confidence: 84%
“…The differential impact of fear between Hong Kong and Taiwan suggests that the association between fear of COVID-19 and personal hygiene practices may need to be induced when the pandemic severity achieves a certain level. Such an observation echoes with a recent study capturing the temporal change in COVID-19 severity in Taiwan that the association between fear and protective behaviors was not significant during March and May 2020 but became significant during May and July 2021 when the largest COVID-19 outbreak in Taiwan was emerging ( 64 ).…”
Section: Discussionsupporting
confidence: 84%
“…A study with 2586 pairs of patients with normal and high CTRs matched by propensity scoring showed that a baseline CTR > 50% was associated with increased mortality and morbidity in patients with heart failure [ 7 ]. Among dialyzed patients infected with COVID-19 in Taiwan, deceased patients had a higher cardiothoracic ratio than surviving patients (0.61 vs. 0.55, p = 0.036) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“… 4 As of 1st July 2021, more than 80% of Taiwanese patients with ESRD had received their first dose of ChAdOx1 nCoV-19 (Oxford-AstraZeneca) vaccine, which was largely the only COVID-19 vaccine available to the nationwide vaccination program before 30th June 2021. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…4 As of 1st July 2021, more than 80% of Taiwanese patients with ESRD had received their first dose of ChAdOx1 nCoV-19 (Oxford-AstraZeneca) vaccine, which was largely the only COVID-19 vaccine available to the nationwide vaccination program before 30th June 2021. 5,6 The ChAdOx1 nCoV-19 vaccine is a non-replicating adenoviral vector vaccine. 7 Its use is correlated with an infrequent yet serious adverse reaction of vaccine-induced thrombosis with thrombocytopenia (VITT).…”
Section: Introductionmentioning
confidence: 99%